Serological response of patients infected with Salmonella typhi. Issue 11 (November 1997) - Chart, H; Rowe, B; Cheesbrough, J S
Abstract : AIMS: To evaluate a rapid immunoblotting procedure for providing evidence of infection with Salmonella typhi using 73 sera from patients infected with S typhi. METHODS: A sodium dodecyl sulphatepolyacrylamide gel electrophoresis (SDS-PAGE)/immunoblotting procedure using lipopolysaccharide (LPS, O = 9, 12) and flagellar (H = d) antigens was used. RESULTS: Seventy two of 73 sera contained antibodies to LPS, 40 sera also contained antibodies to H = d flagellar antigens. Analysis of acute and convalescent sera showed that only 62% of patients produced antibodies to flagellar antigens. CONCLUSIONS: The SDS-PAGE/immunoblotting procedure provided a rapid method for providing serological evidence of infection with S typhi.